The idea of Anglo-Saxon England 1066-1901 : remembering, forgetting, deciphering, and renewing the past - Niles, John D.; Ohio Library and Information Network (Chichester, UK ; Malden, MA : John Wiley & Sons, Blackwell, 2015)
The Idea of Anglo Saxon England, 1066-1901 presents the first systematic review of the ways in which Anglo-Saxon studies have evolved from their beginnings to the twentieth century Tells the story of how the idea of Anglo-Saxon England evolved from the Anglo-Saxons themselves to the Victorians, serving as a myth of origins for the English people, their language, and some of their most cherished institutions Combines original research with established scholarship to reveal how current conceptions of English identity might be very different if it were not for the discovery - and invention - of
The impact of the Norman conquest -- The discovery of Anglo-Saxon England in Tudor times -- British antiquaries and the Anglo-Saxon past -- The founding of a discipline 1600-1700 -- A period of consolidation 1700-1800 -- The Romantics and the discovery of Old English verse -- The triumph of philology -- Old English studies in North America -- Anglo-Saxon England and the empire
Includes bibliographical references and index
Keywords: Anglo-Saxons -- Historiography; English philology -- Old English, ca. 450-1100 -- History; United Kingdom -- History -- Anglo-Saxon period, 449-1066 -- Historiography; Electronic books; History